Dihydromyricetin functions as a tumor suppressor in hepatoblastoma by regulating SOD1/ROS pathway - Guo, Tong; Wang, Xitong; Zhang, Gensheng; Xia, Tian; Zhu, Runzhi; Tou, Jinfa (Frontiers in Oncology, 2023)
Hepatoblastoma has an unsatisfactory prognosis, and traditional chemotherapy has strong side effects. Dihydromyricetin is a flavonoid extracted from a woody vine of the genus Serpentine in the family Vitaceae, with effects such as preventing alcoholic liver and reducing the incidence of liver cancer. However, the effect of DHM on hepatoblastoma and its specific pathway are still unclear. The purpose of this study was to investigate the effects of DHM on children's hepatoblastoma and its related mechanisms. CCK-8 assay, flow cytometry, fluorescence microscopy and the western blot were carried out to detect the anticancer effects of DHM on hepatoblastoma cells. We found that DHM was able to inhibit the growth and increase cellular mortality in HuH-6 and HepG2 cells. Furthermore, DHM decreased the intracellular ROS level and increased the expression of SOD1. ROS scavenger NAC promoted apoptosis, while the use of SOD1 inhibitor LCS-1 weakened the ROS scavenging effect of DHM , and to some extent reduced the killing effect of DHM on hepatoblastoma cells. These results indicate that DHM could induce hepatoblastoma cell apoptosis by targeting SOD1 to down-regulate ROS. Therefore, DHM may be a novel candidate for inhibiting hepatoblastoma growth and deserves further study.